Analysis of α-Synuclein Pathology in PINK1 Knockout Rat Brains - Creed, Rose B.; Goldberg, Matthew S. (Frontiers in Neuroscience, 2019)
Mutations in PTEN induced kinase 1 (PINK1) cause autosomal recessive Parkinson’s disease (PD). The main pathological hallmarks of PD are loss of dopaminergic neurons in the substantia nigra pars compacta, and the formation of protein aggregates containing α-synuclein. Previous studies of PINK1 knockout (PINK1-/-) rats have reported mitochondrial dysfunction, locomotor behavioral deficits, loss of neurons in the substantia nigra, and α-synuclein aggregates in various brain regions. We sought to characterize PINK1-/- rats in more detail specifically with respect to α-synuclein pathology because abnormal α-synuclein has been implicated genetically, biophysically and neuropathologically as a mechanism of PD pathogenesis. Moreover, the spontaneous formation of α-synuclein aggregates—without α-synuclein overexpression, injection or toxin administration—is a rare and important characteristic for an animal model of PD. We observed α-synuclein-immunoreactive aggregates in various brain regions of PINK1-/- rats including cortex, thalamus, striatum and ventral midbrain, but nowhere in wild-type (WT) rats. Co-imunofluorescence showed that the α-synuclein-immunoreactive aggregates are both thioflavin S and ubiquitin positive. Many cells in the brains of PINK1-/- rats but not WT rats contained protease-resistant α-synuclein. Total synuclein protein levels were unchanged, however, biochemical fractionation showed a significant shift of α-synuclein from the cytosolic fraction to the synaptic vesicle-enriched fraction of PINK1-/- brain homogenates compared to WT. This data indicates that PINK1 deficiency results in abnormal α-synuclein localization, protease resistance and aggregation in vivo. The PINK1-/- rat could be a useful animal model to study the role of abnormal α-synuclein in PD-related neurodegeneration.